DRONE TECHNOLOGY FOR CONTOUR MAPPING: CASE STUDY AT P3SON HAMBALANG - Samuel Jonson Sutanto; Banata Wachid Ridwan (Pusat Litbang Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2016)
Fast, reliable, and accurate topography measurement is needed for a study and evaluation of P3SON Hambalang area. Experimental Station for Sabo, therefore, was given a mandate to perform the topography measurement. Measurement has been carried out using fotogrammetry technique of remote sensing photos captured by drone. The results of drone measurement are Digital Surface Model (DSM), Digital Terain Model (DTM), and the final result is a contour map, which have high resolution data of 5 cm. The whole processes starting from field measurement until final results are obtained require around 4 to 5 working days, without any significant obstacles during both measurement and analysis. Due to the high-resolution result, fast, and cheap, it is foreseen that fotogrammetry technique using drone will be used more often in the future for topography measurement. However, drone topography measurements experience a difficulty in the non-vulkanic rivers (river with water table). The riverbed cannot be well measured by drone, especially for the rivers with high sediment concentration such in general rivers in Indonesia.